Inflation as a global problem - Hinshaw, Randall Weston; Johns Hopkins University; Claremont Graduate School (Baltimore : Johns Hopkins University Press, 1972)
The theme o the 1971 Bologna conference was inflation as a global problem. In the past, inflation has generally been thought of a s a national problem, and there have been innumerable cases of national inflation, or even or "hyperinflation," unaccompanied by inflationary tendencies in the rest of the world.
Report of a conference on international monetary problems held at the Johns Hopkins Center in Bologna, Italy, Apr. 15-18, 1971, and sponsored jointly by Johns Hopkins and Claremont Graduate School.
Proceedings of the 3d of a series of meetings; proceedings of the 2d are entered under Claremont International Monetary Conference, 1969; the 4th, under Bologna-Claremont International Monetary Conference, Claremont, Calif., 1973.
Loans
osa; 8/08/18
Keywords: Inflation (Finance); International finance